Short term rehabilitation and ankle instability - Lee, K.-Y.; Lee, H.-J.; Kim, S. E.; Choi, P.-B.; Song, S.-H.; Jee, Y.-S. (International Journal of Sports Medicine, 2012)
Chronic ankle instability (CAI) after ankle sprains has been shown to cause foot and ankle disability. Although rehabilitation programs for patients with CAI have been performed in related studies, few researchers have studied overall performance including pain, balance, and isokinetic torque. The purpose of this study was to determine if a short-term rehabilitation program that addressed range of motion (ROM), functional muscular performance, and neuromuscular control, can improve the foot/ankle disability index (FADI), FADI-Sport, ROM, star excursion balance test (SEBT), and isokinetic torque for patients with CAI. Prior to the experiment, we investigated the principal injury site through an administered questionnaire on 236 potential participants, and selected 18 male subjects aged between 21 and 23 years. 9 subjects (rehabilitation group, RG) with unilateral CAI took part in the rehabilitation program for 4 weeks, whereas 9 subjects (control group, CG) did not participate in that program. The results were as follows; the RG significantly increased FADI, FADI-Sport scores, and ROM on the injured limb compared with the CG. Also, the RG had greater SEBT reaches and improvements in isokinetic torque compared with the CG. In conclusion, these results demonstrate that a short-term rehabilitation program can improve functional limitations in patients with CAI.